PENGARUH FISIOTERAPI DADA TERHADAP KUANTITAS TIDUR PASIEN PENYAKIT PARU OBSTRUKSI KRONIK - Akbar, Orlando Riki (JURNAL MEDIA KESEHATAN, 2013)
Individuals with Chronic Obstructive Pulmonary Disease ( COPD ) often experience a disruption in the fulfillment of the need for rest and sleep . The results of the survey conducted in inpatient RSUD Dr. M. Yunus Bengkulu earned 5 COPD patients experience sleep disturbances and did not know act chest physiotherapy and omissions chest physiotherapy to increase the quantity of sleep of patients with COPD . This type of research is Pre Experiment with using design one group pre and post test . Population in this research is that COPD patients are running the entire hospitalization in Melati, Kenanga, dan Teratai RSUD Dr. M. Yunus Bengkulu . Samples taken by accidental sampling of 30 samples. Data analysis of the 30 respondents were Univariate and Bivariate by paired t - test test at α 5 % . The results showed that there was an increase in the average COPD patient sleep after nursing actions chest physiotherapy (p = 0.000) . Hospital room nurse suggested to perform nursing interventions to improve sleep in COPD patients with chest physiotherapy.